Apartheid: wrong for South Africans, wrong for Palestinians - End Israeli apartheid!
With statements on Israeli apartheid by resp. former South African president Nelson Mandela and nobel prize winner Archbishop Desmond Tutu, and with comparison between bantustans in South Africa and in West Bank.